Concrete Repair Materials
A concrete repair material with specific resin and monomer components addresses thixotropy, curability, and alkali resistance issues, offering improved adhesion and odor control for concrete surfaces.
Patent Information
- Application Number
- JP2020154456
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-09-15
AI Technical Summary
Existing concrete protection materials lack thixotropy, curability, low odor, and wet adhesion, and are insufficiently alkali-resistant, leading to issues like sagging and poor adhesion on wet concrete surfaces.
A concrete repair material comprising a resin with polymerizable unsaturated groups at both ends, unsaturated polyester, monofunctional (meth)acrylic monomer with a flash point of 70°C or higher, polyfunctional (meth)acrylic monomer, cyclodextrin derivative, and silica fine particles, which enhances thixotropy, curability, and wet adhesion while providing alkali resistance.
The material exhibits excellent thixotropy, low odor, and provides a coating film with superior wet adhesion and alkali resistance, suitable for various concrete types.
Smart Images

Figure 0007615578000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a concrete repair material. [Background technology]
[0002] One of the causes of deterioration of concrete structures is corrosion of the internal rebars caused by the infiltration of rainwater, etc. To address this, methods of protecting the concrete surface with a coating material and preventing spalling by attaching fibers or the like are adopted. The materials used are required to have fast curing properties that allow construction to be completed in a short time, adhesion to concrete that has become wet due to rain, low odor for environmental reasons, etc. As such materials, concrete protection materials containing urethane (meth)acrylate, radical polymerizable monomer, cyclodextrin and / or its derivatives, and unsaturated polyester have been proposed (for example, see Patent Document 1).
[0003] However, this material has insufficient alkali resistance, and when applied to the wall surface of a concrete structure, etc., it has insufficient thixotropy and has a problem of sagging. Therefore, a material that can give a coating film that is excellent in thixotropy, low odor, excellent in curing, wet adhesion, and alkali resistance has been desired. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-229707 A Summary of the Invention [Problem to be solved by the invention]
[0005] The problem to be solved by the present invention is to provide a concrete protective material which is capable of providing a coating film which is excellent in thixotropy, low in odor, excellent in curing properties, and excellent in wet adhesion and alkali resistance. [Means for solving the problem]
[0006] As a result of intensive research conducted by the present inventors to solve the above-mentioned problems, they have found that the above-mentioned problems can be solved by a concrete repair material containing a resin having polymerizable unsaturated groups at both ends, an unsaturated polyester, a monofunctional (meth)acrylic monomer having a flash point of 70°C or higher, a polyfunctional (meth)acrylic monomer, a cyclodextrin derivative, and silica fine particles, and have completed the present invention.
[0007] That is, the present invention provides a concrete repair material characterized by containing a resin (A) having polymerizable unsaturated groups at both ends, an unsaturated polyester (B), a monofunctional (meth)acrylic monomer (C) having a flash point of 70°C or higher, a polyfunctional (meth)acrylic monomer (D), a cyclodextrin derivative (E), and silica microparticles (F). Effect of the Invention
[0008] The concrete repair material of the present invention can be suitably used as a repair material for various types of concrete because it provides a coating film that is excellent in thixotropy, low odor, curing properties, and excellent in wet adhesion and alkali resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The concrete protection material of the present invention contains a resin (A) having polymerizable unsaturated groups at both ends, an unsaturated polyester (B), a monofunctional (meth)acrylic monomer (C) having a flash point of 70°C or higher, a polyfunctional (meth)acrylic monomer (D), a cyclodextrin derivative (E), and silica fine particles (F).
[0010] In the present invention, the term "(meth)acrylic monomer" refers to either or both of an acrylic monomer and a methacrylic monomer, the term "(meth)acrylate" refers to either or both of a methacrylate and an acrylate, and the term "(meth)acryloyl" refers to either or both of an acryloyl and a methacryloyl.
[0011] Examples of the resin (A) having polymerizable unsaturated groups at both ends include epoxy (meth)acrylate, polyester (meth)acrylate, and urethane (meth)acrylate. These resins (A) having polymerizable unsaturated groups at both ends may be used alone or in combination of two or more.
[0012] As the epoxy (meth)acrylate, for example, a compound obtained by reacting a bisphenol type epoxy compound or an epoxy compound obtained by mixing a bisphenol type epoxy compound with a novolac type epoxy compound with an unsaturated monobasic acid by a conventionally known method can be used.
[0013] Examples of the bisphenol type epoxy compound that can be used include a glycidyl ether type epoxy compound having two or more epoxy groups in one molecule obtained by reacting epichlorohydrin with bisphenol A or bisphenol F, a dimethylglycidyl ether type epoxy compound obtained by reacting methylepichlorohydrin with bisphenol A or bisphenol F, and an epoxy compound obtained by reacting an alkylene oxide adduct of bisphenol A with epichlorohydrin or methylepichlorohydrin. These epoxy compounds may be used alone or in combination of two or more.
[0014] As the novolac type epoxy compound, for example, an epoxy compound obtained by reacting phenol novolac or cresol novolac with epichlorohydrin or methyl epichlorohydrin can be used. These epoxy compounds may be used alone or in combination of two or more kinds.
[0015] Examples of the unsaturated monobasic acid that can be used include (meth)acrylic acid, cinnamic acid, crotonic acid, monomethyl maleate, monopropyl maleate, monobutene maleate, sorbic acid, mono(2-ethylhexyl) maleate, etc. These unsaturated monobasic acids may be used alone or in combination of two or more kinds.
[0016] The polyester (meth)acrylate may be, for example, a saturated polyester or an unsaturated polyester having two or more (meth)acryloyl groups in one molecule. The saturated polyester is a product of a condensation reaction between a saturated dibasic acid and a polyhydric alcohol, and the unsaturated polyester is a product of a condensation reaction between an α,β-unsaturated dibasic acid and a polyhydric alcohol, both of which have a (meth)acryloyl group at the end.
[0017] The saturated dibasic acid, α,β-unsaturated dibasic acid and polyhydric alcohol may be the same as those used in the synthesis of the unsaturated polyester (B) described below.
[0018] The polyester (meth)acrylate may be produced by reacting a saturated polyester or an unsaturated polyester with glycidyl (meth)acrylate by a known method.
[0019] As the urethane (meth)acrylate, for example, one obtained by reacting a polyol, a polyisocyanate, and a (meth)acrylic compound having a hydroxyl group or an isocyanate group by a conventionally known method can be used.
[0020] Examples of the polyol that can be used include polyester polyol, polycarbonate polyol, polyether polyol, acrylic polyol, caprolactone polyol, butadiene polyol, etc. These polyols may be used alone or in combination of two or more kinds.
[0021] Examples of the polyisocyanate include aromatic diisocyanates such as phenylene diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, and naphthalene diisocyanate; aliphatic or alicyclic diisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, xylylene diisocyanate, and tetramethylxylylene diisocyanate; and aromatic polyisocyanates such as xylylene diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, polyphenylene polymethylene polyisocyanate, formalin condensate of methylene diphenyl diisocyanate, and carbodiimide modified product of 4,4'-diphenylmethane diisocyanate. These polyisocyanates may be used alone or in combination of two or more.
[0022] Examples of the (meth)acrylic compound having a hydroxyl group include (meth)acrylic acid alkyl esters having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; polyethylene glycol monoacrylate, polypropylene glycol monoacrylate, etc. These compounds may be used alone or in combination of two or more.
[0023] Examples of the (meth)acrylic compound having an isocyanate group that can be used include 2-(meth)acryloyloxyethyl isocyanate, 2-(2-(meth)acryloyloxyethyloxy)ethyl isocyanate, 1,1-bis((meth)acryloyloxymethyl)ethyl isocyanate, etc. These compounds may be used alone or in combination of two or more.
[0024] The number average molecular weight of the resin (A) is preferably 500 to 4,000, since this can further improve workability and curing properties.
[0025] The content of the resin (A) in the concrete repair material is preferably 10 to 50 mass %, and more preferably 20 to 40 mass %, because this allows for further improved curing properties.
[0026] As the unsaturated polyester (B), for example, one obtained by reacting a dibasic acid including an α,β-unsaturated dibasic acid with a polyhydric alcohol by a conventionally known method can be used.
[0027] Examples of the α,β-unsaturated dibasic acid that can be used include maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, etc. These dibasic acids may be used alone or in combination of two or more kinds.
[0028] As a dibasic acid that can be used other than the α,β-unsaturated dibasic acid, a saturated dibasic acid can be used, for example, phthalic acid, phthalic anhydride, halogenated phthalic anhydride, isophthalic acid, terephthalic acid, tetrahydrophthalic acid, tetrahydrophthalic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride, hexahydroterephthalic acid, hexahydroisophthalic acid, succinic acid, malonic acid, glutaric acid, adipic acid, sebacic acid, 1,12-dodecane diacid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid anhydride, 4,4'-biphenyldicarboxylic acid, and dialkyl esters thereof can be used. These dibasic acids can be used alone or in combination of two or more.
[0029] Examples of the polyhydric alcohol include ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, 1,3-butanediol, neopentyl glycol, hydrogenated bisphenol A, 1,4-butanediol, and alkylene oxide adducts of bisphenol A. Examples of polyhydric alcohols that can be used include 1,2,3,4-tetrahydroxybutane, glycerin, trimethylolpropane, 1,3-propanediol, 1,2-cyclohexane glycol, 1,3-cyclohexane glycol, 1,4-cyclohexane glycol, 1,4-cyclohexanedimethanol, paraxylene glycol, bicyclohexyl-4,4'-diol, 2,6-decalyl glycol, 2,7-decalyl glycol, etc. These polyhydric alcohols may be used alone or in combination of two or more kinds.
[0030] The content of the unsaturated polyester (B) in the concrete repair material is preferably from 1 to 30 mass %, and more preferably from 5 to 20 mass %, since the curing property can be further improved.
[0031] Examples of the monofunctional (meth)acrylic monomer (C) having a flash point of 70° C. or higher include (meth)acrylic monomers having an alicyclic structure such as isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate; 2-ethylbutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, n-butyl (meth)acrylate, n-hexyl (meth)acrylate, and n-butyl (meth)acrylate; aliphatic (meth)acrylic monomers such as ethylhexyl (meth)acrylate, heptyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, dodecyl (meth)acrylate, 3-methylbutyl (meth)acrylate, isooctyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, neopentyl (meth)acrylate, hexadecyl (meth)acrylate, and isoamyl (meth)acrylate; ethylene oxide and / or propylene oxide such as methoxypolyethylene glycol (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-methoxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate having an added mole number of oxyethylene in the range of 1 to 15, methoxypolypropylene glycol (meth)acrylate having an added mole number of oxypropylene in the range of 1 to 15, ethoxy-diethylene glycol (meth)acrylate, and ethyl carbitol (meth)acrylate; (meth)acrylic monomers having an oxide; (meth)acrylic monomers having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; aromatic (meth)acrylic monomers, such as benzyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol acrylate, phenyl (meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate;(Meth)acrylic monomers having nitrogen atoms such as (meth)acrylamide, dimethyl(meth)acrylamide, acryloylmorpholine, dimethylaminopropyl(meth)acrylamide, isopropyl(meth)acrylamide, diethyl(meth)acrylamide, diacetone(meth)acrylamide, and hydroxyethylacrylamide can be used, and among these, (meth)acrylic monomers having nitrogen atoms, (meth)acrylic monomers having hydroxyl groups, and (meth)acrylic monomers having ethylene oxide and / or propylene oxide are preferred because they can further suppress odor. These (meth)acrylic monomers may be used alone or in combination of two or more.
[0032] The flash point in the present invention is a value measured by a Seta closed cup flash point measurement.
[0033] The content of the (meth)acrylic monomer (C) in the concrete repair material is preferably 10 to 70 mass%, more preferably 20 to 60 mass%, and even more preferably 30 to 50 mass%, because excellent curing properties can be achieved with low viscosity.
[0034] Examples of the polyfunctional (meth)acrylic monomer (D) include di(meth)acrylate compounds such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol di(meth)acrylate, 1,4-cyclohexanedimethanol di(meth)acrylate, and trimethylolpropane di(meth)acrylate; and polyfunctional (meth)acrylates having three or more functional groups such as trimethylolpropane triacrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate. Among these, di(meth)acrylate compounds are preferred because they provide excellent wet surface adhesion.
[0035] The content of the polyfunctional (meth)acrylic monomer (D) in the concrete repair material is preferably 3 to 50 mass%, more preferably 5 to 40 mass%, and even more preferably 10 to 30 mass%, because excellent curing properties can be achieved with low viscosity.
[0036] The mass ratio (C / D) of the (meth)acrylic monomer (C) to the polyfunctional (meth)acrylic monomer (D) is preferably 100 / 0 to 30 / 70, and more preferably 90 / 10 to 50 / 50, in order to further improve the balance between the curability and the wet surface adhesion.
[0037] Examples of the cyclodextrin derivative (E) include cyclodextrin; alkylated cyclodextrin, acetylated cyclodextrin, and hydroxyalkylated cyclodextrin, in which the hydrogen atom of the hydroxyl group of the glucose unit of cyclodextrin is replaced with another functional group. In addition, any of α-cyclodextrin consisting of 6 glucose units, β-cyclodextrin consisting of 7 glucose units, and γ-cyclodextrin consisting of 8 glucose units can be used as the cyclodextrin skeleton in cyclodextrin and cyclodextrin derivatives. These cyclodextrin derivatives (E) may be used alone or in combination of two or more kinds. Among these, methylated β-cyclodextrin is preferred because of its excellent solubility in resin.
[0038] The content of the cyclodextrin derivative (E) in the concrete repair material is preferably 0.1 to 5 mass %, and more preferably 0.2 to 3 mass %, because the wet surface adhesion is improved.
[0039] Examples of the silica fine particles (F) include dry silica and wet silica, with dry silica being preferred since it provides a further improvement in thixotropy.
[0040] The average primary particle diameter of the silica fine particles (F) is preferably from 5 to 50 nm, since this further improves thixotropy.
[0041] The silica fine particles (F) preferably have a hydrophobic surface, since this further improves the thixotropy.
[0042] The content of the silica particles (F) in the concrete repair material is preferably from 0.1 to 10 mass %, more preferably from 0.5 to 5 mass %, in view of excellent workability.
[0043] The concrete repair material of the present invention contains the resin (A), the unsaturated polyester (B), the monofunctional (meth)acrylic monomer (C), the polyfunctional (meth)acrylic monomer (D), the cyclodextrin derivative (E), and the silica microparticles (F) as essential components, and may contain other additives, etc., as necessary.
[0044] Examples of the other additives include polymerization inhibitors, antioxidants, light stabilizers, solvents, rust inhibitors, sensitizers, leveling agents, rheology control agents, tackifiers, antistatic agents, flame retardant curing agents, curing accelerators, pigments, fillers, reinforcing materials, aggregates, and petroleum waxes.
[0045] The active energy rays that harden the concrete repair material of the present invention include ionizing radiation such as ultraviolet rays, electron beams, alpha rays, beta rays, and gamma rays, and specific energy sources or hardening devices include, for example, germicidal lamps, ultraviolet fluorescent lamps, carbon arcs, xenon lamps, high-pressure mercury lamps for copying, medium-pressure or high-pressure mercury lamps, ultra-high-pressure mercury lamps, electrodeless lamps, metal halide lamps, fluorescent chemical lamps, ultraviolet rays using natural light or the like as a light source, or electron beams from scanning or curtain-type electron beam accelerators.
[0046] The concrete repair material of the present invention can be used as a protective material for concrete such as cement concrete, asphalt concrete, mortar concrete, resin concrete, water-permeable concrete, and ALC (Autoclaved Lightweight Aerated Concrete) boards.
[0047] The concrete protective material of the present invention can be suitably used as a repair material for various types of concrete because it gives a coating film that is excellent in thixotropy, low odor, curing property, wet adhesion and alkali resistance. EXAMPLES
[0048] The present invention will be described in more detail below with reference to specific examples. The acid value was measured in accordance with JIS-K-6901, and the average molecular weight was measured under the following GPC measurement conditions.
[0049] [GPC measurement conditions] Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series. "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 4 mg / mL in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following monodisperse polystyrene.
[0050] (monodisperse polystyrene) "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation
[0051] (Synthesis Example 1: Synthesis of Resin (A-1) Having Polymerizable Unsaturated Groups at Both Ends) A four-neck flask equipped with a thermometer, a stirrer, an inert gas inlet, and a reflux condenser was charged with 1,850 parts by mass of Epicron 850 (manufactured by DIC Corporation), which is an epoxy equivalent obtained by reacting bisphenol A with epichlorohydrin, 860 parts by mass of acrylic acid, 1.36 parts by mass of hydroquinone, and 10.8 parts by mass of triethylamine, and the mixture was heated to 120°C and reacted for 10 hours to obtain a resin (A-1) having polymerizable unsaturated groups at both ends as an epoxy acrylate with a molecular weight of 512 and an acid value of 3.5.
[0052] (Synthesis Example 2: Synthesis of Resin (A-2) Having Polymerizable Unsaturated Groups at Both Ends) A four-neck flask equipped with a thermometer, a stirrer, an inert gas inlet, and a reflux condenser was charged with 250 parts by mass of neopentyl glycol, 100 parts by mass of propylene glycol, 390 parts by mass of adipic acid, and 100 parts by mass of maleic anhydride, and 0.5 parts by mass of monobutyltin oxide was added as an esterification catalyst, and the mixture was reacted for 11 hours at 205° C. Thereafter, the mixture was cooled to 140° C., and then 25 parts by mass of glycidyl methacrylate was added and reacted for 10 hours to obtain a resin (A-2) having polymerizable unsaturated groups at both ends as a polyester (meth)acrylate having a number average molecular weight of 4,150.
[0053] (Synthesis Example 3: Synthesis of Resin (A-3) Having Polymerizable Unsaturated Groups at Both Ends) A reaction vessel equipped with a thermometer, a stirrer, an inert gas inlet, an air inlet and a reflux condenser was charged with 500 parts by mass of polypropylene glycol having a number average molecular weight of 1000 and 172 parts by mass of tolylene diisocyanate, and reacted for 2 hours at 80°C under a nitrogen stream. Since the NCO equivalent was 600, which was almost the theoretical equivalent value, it was cooled to 50°C. Under an air stream, 0.07 parts by mass of hydroquinone was added, and 135 parts by mass of 2-hydroxyethyl methacrylate was added, and the reaction was carried out at 90°C for 4 hours. When the NCO% became 0.1% or less, 0.07 parts by mass of tertiary butyl catechol was added, and a resin (A-3) having polymerizable unsaturated groups at both ends was obtained as a urethane methacrylate having a number average molecular weight of 1,580.
[0054] (Synthesis Example 4: Synthesis of Unsaturated Polyester (B-1)) A reaction vessel equipped with a thermometer, a stirrer, an inert gas inlet, and a reflux condenser was charged with 231 parts by mass of triethylene glycol, 80 parts by mass of diethylene glycol, 102 parts by mass of phthalic anhydride, 210 parts by mass of 3-methyltetrahydrophthalic acid, 0.3 parts by mass of dibutyltin oxide, and 0.1 parts by mass of methylhydroquinone, and reacted for 4 hours at 205° C. The mixture was cooled to 150° C., and 34 parts by mass of maleic anhydride was added and reacted for 4 hours at 190° C. to obtain an unsaturated polyester (B-1) with an acid value of 12.0.
[0055] (Example 1: Preparation and evaluation of concrete repair material (1)) In a light-shielding container equipped with a stirrer, reflux condenser, and thermometer, 30 parts by mass of resin (A-1) having polymerizable unsaturated groups at both ends, 10 parts by mass of unsaturated polyester (B-1), 0.5 parts by mass of methylated β-cyclodextrin, 30 parts by mass of dicyclopentenyloxyethyl methacrylate, 10 parts by mass of 2-hydroxyethyl methacrylate, 20 parts by mass of diethylene glycol dimethacrylate, 3 parts by mass of silica fine particles (Tokuyama Corporation's "Reolosil QS-102", dry silica; hereinafter abbreviated as silica fine particles (F-1)), and 1.5 parts by mass of a rheology control agent (BYK's "BYK R-605") were stirred and mixed to obtain a concrete repair material (1).
[0056] [Evaluation of thixotropy] The viscosity of the concrete repair material (1) obtained above was measured using a Type i BM viscometer in Table 7 in accordance with "5.5.1 When using the Brookfield type viscometer method" of JIS K6901:2008, and the TI value (viscosity value at 6 rpm / viscosity value at 60 rpm) was calculated, and the thixotropy was evaluated according to the following criteria. ○: TI value is 4 or more ×: TI value is less than 4
[0057] [Preparation of evaluation samples] 0.25 parts by mass of 8% by mass cobalt octylate, 0.5 parts by mass of a toluidine compound isopropanol solution ("RP-191" manufactured by DH Material Co., Ltd.), and 1 part by mass of a 40% by mass benzoyl peroxide solution were added to and mixed with 50 parts by mass of the concrete repair material (1) obtained above to obtain an evaluation sample (1).
[0058] [Odor evaluation] In an environment of 23°C, the above-obtained evaluation sample (1) was 0.2 kg / m 2 The odor when the paint was applied to a slate board with a brush was evaluated by sensory judgment, and the odor was rated according to the following criteria. ○: No odor or slight odor ×: Odor
[0059] [Evaluation of hardening] The evaluation sample (1) obtained above was placed on a slate board at a pressure of 0.2 kg / m 2 The time until the composition became tack-free when touched with a finger was measured at 23° C., and the curability was evaluated according to the following criteria. ○: Less than 90 minutes ×: 90 minutes or more
[0060] [Evaluation of wet surface adhesion] The evaluation sample (1) obtained above was soaked in water for one day, then taken out and wiped to remove water droplets. 2 The coating was left to cure for one day, and then pulled vertically using a Kenken tensile tester ("Technostar RT-3000LD" manufactured by Sanko Techno Co., Ltd.) to measure the peel strength and evaluate the wet surface adhesion according to the following criteria. 〇1.5N / mm 2 End ×1.5N / mm 2 less than
[0061] [Evaluation of alkali resistance] The evaluation sample (1) obtained above was applied to a mortar measuring 70 x 70 x 20 mm at a rate of 0.2 kg / m using a brush. 2 The specimens obtained by coating were partially immersed in a saturated calcium hydroxide aqueous solution and cured for 30 days at 40°C. After 30 days, the appearance of the specimens was visually observed and the alkali resistance was evaluated according to the following criteria. 〇: No change ×: Blisters or cracks
[0062] (Examples 2 and 3: Preparation and evaluation of concrete repair materials (2) and (3)) Except for changing the resin (A-1) having polymerizable unsaturated groups at both ends used in Example 1 to resin (A-2) or (A-3) having polymerizable unsaturated groups at both ends, concrete repair materials (2) and (3) were prepared in the same manner as in Example 1, and their physical properties were evaluated.
[0063] (Comparative Examples 1 and 2: Preparation and Evaluation of Concrete Repair Materials (R1) and (R2)) Except for using the composition of Example 1 as shown in Table 1, concrete repair materials (R1) and (R2) were prepared in the same manner as in Example 1, and then the physical properties were evaluated.
[0064] Table 1 shows the compositions and evaluation results of the concrete repair materials (1) to (3) and (R1) to (R2) obtained above.
[0065] [Table 1]
[0066] It was confirmed that the concrete repair materials of the present invention in Examples 1 to 3 gave coating films that were excellent in thixotropy, had low odor, and cured well, and had excellent wet adhesion and alkali resistance.
[0067] Comparative Example 1 is an example that does not contain the unsaturated polyester (B) and the (meth)acrylic monomer, but has a high viscosity, insufficient thixotropy, and poor workability.
[0068] Comparative Example 2 is an example that does not contain the polyfunctional (meth)acrylic monomer (D), but the alkali resistance of the resulting coating film was insufficient.
Claims
[Claim 1] A concrete repair material containing a resin (A) having polymerizable unsaturated groups at both ends, an unsaturated polyester (B), a monofunctional (meth)acrylic monomer (C) having a flash point of 70° C. or more, a polyfunctional (meth)acrylic monomer (D), a cyclodextrin derivative (E), and silica fine particles (F), wherein the resin (A) is one or more resins selected from the group consisting of epoxy (meth)acrylates, polyester (meth)acrylates, and urethane (meth)acrylates, A concrete repair material characterized in that the content of (A) is 10 to 50 mass%, the content of the unsaturated polyester (B) is 1 to 30 mass%, the content of the monofunctional (meth)acrylic monomer (C) having a flash point of 70°C or higher is 10 to 70 mass%, the content of the polyfunctional (meth)acrylic monomer (D) is 3 to 50 mass%, the content of the cyclodextrin derivative (E) is 0.1 to 5 mass%, and the content of the silica fine particles (F) is 0.1 to 10 mass%.
Citation Information
Patent Citations
Resin composition, substrate impregnating material and coating material
JP1997157336A
Radically-polymerizable resin composition, and civil engineering and construction material
JP2015052080A
Radical-polymerizable composition, concrete repair material, and primer for road
JP2015229707A
Resin composition for concrete structure repair
JP2020111947A
Radical polymerizable resin composition and primer for civil engineering and construction
WO2016171034A1